2013
DOI: 10.1002/jbmr.2048
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular Bone Score (TBS) Predicts Vertebral Fractures in Japanese Women Over 10 Years Independently of Bone Density and Prevalent Vertebral Deformity: The Japanese Population-Based Osteoporosis (JPOS) Cohort Study

Abstract: Bone strength is predominantly determined by bone density, but bone microarchitecture also plays an important role. We examined whether trabecular bone score (TBS) predicts the risk of vertebral fractures in a Japanese female cohort. Of 1950 randomly selected women aged 15 to 79 years, we analyzed data from 665 women aged 50 years and older, who completed the baseline study and at least one follow-up survey over 10 years, and who had no conditions affecting bone metabolism. Each survey included spinal imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 50 publications
(71 reference statements)
8
111
1
4
Order By: Relevance
“…We did not detect changes in cortical bone, a large determinant of bone strength and nonvertebral fracture risk. However, trabecular bone is important for the prevention of osteoporosis, particularly for the impediment of vertebral fractures, which result in pain, functional disability, and decreased quality of life (Gerdhem 2013;Iki et al 2014). Therefore, the resulting increases in trabecular bone volume afforded by PHD2 and PHD3 inactivation may have important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…We did not detect changes in cortical bone, a large determinant of bone strength and nonvertebral fracture risk. However, trabecular bone is important for the prevention of osteoporosis, particularly for the impediment of vertebral fractures, which result in pain, functional disability, and decreased quality of life (Gerdhem 2013;Iki et al 2014). Therefore, the resulting increases in trabecular bone volume afforded by PHD2 and PHD3 inactivation may have important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…TBS is less expensive and more easily accessible than CT or MRI for wide-spread clinical implementation or as an outcome in large research studies. The very first TBS reports showed applications for the prediction of fracture risk in osteoporosis (39)(40)(41), have added value in those individuals with bone density outside of the osteoporosis range (42) and monitoring of treatment effects (43,44), and similarly, TBS may find an application in other conditions such as primary hyperparathyroidism (45), hypercortisolism (46), rheumatoid arthritis (47), and diabetes-related bone disease (48). A major advantage is that it can be derived from DXA scans using dedicated post-processing software.…”
Section: Dxa-additional Parametersmentioning
confidence: 99%
“…A number of cross-sectional (24)(25)(26)(27)(28)(29) and prospective (15,16,30,31) studies have shown an association between LS TBS and vertebral, hip, and other types of osteoporotic fractures in postmenopausal women. A recent published cross-sectional study has also demonstrated that TBS is associated with fractures in men (32).…”
Section: Association Of Tbs With Fracture Riskmentioning
confidence: 99%
“…Data from prospective studies are summarized in table 3 (15,16,30,31). The Manitoba study was the largest one to examine the ability of LS TBS to predict fracture risk (16).…”
Section: Prospective Studiesmentioning
confidence: 99%